European association of urology section of urolithiasis and international alliance of urolithiasis joint consensus on retrograde intrarenal surgery for the management of renal stones - Zeng, Guohua; Zhao, Zhijian; Mazzon, Giorgio; Pearle, Margaret; Choong, Simon; Skolarikos, Andreas; Denstedt, John; Seitz, Christian; Olvera Pasada, Daniel; Fiori, Cristian; Bosio, Andrea; Papatsoris, Athanasios; et al. (Elsevier B.V., 2022)
Background: Retrograde intrarenal surgery (RIRS) has become the preferred treatment modality for nephrolithiasis. However, because of ongoing uncertainties regarding the optimal perioperative management, operative technique, and postoperative follow-up, as well as a lack of standardization for outcome reporting, consensus is needed to achieve more uniform clinical practice worldwide. Objective: To develop recommendations for RIRS on the basis of existing data and expert consensus. Design, setting, and participants: A protocol-driven, three-phase study was conducted by the European Association of Urology Section of Urolithiasis (EULIS) and the International Alliance of Urolithiasis (IAU). The process included: (1) a nonsystematic review of the literature to define domains for discussion; (2) a two-round modified Delphi survey involving experts in this field; and (3) an additional group meeting and third-round survey involving 64 senior representative members to formulate the final conclusions. Outcome measurements and statistical analysis: The results from each previous round were returned to the participants for re-evaluation of their decisions during the next round. The agreement threshold was set at 70%. Results and limitations: The panel included 209 participants who developed 29 consensus statements on the following topics of interest: (1) perioperative infection management; (2) perioperative antithrombotic therapy; (3) fundamentals of the operative technique; and (4) standardized outcome reporting. Although this consensus can be considered as a useful reference for more clinically oriented daily practice, we also acknowledge that a higher level of evidence from further clinical trials is needed. Conclusions: The consensus statements aim to guide and standardize clinical practice and research on RIRS and to recommend standardized outcome reporting. Patient summary: An international consensus on the best practice for minimally invasive surgery for kidney stones was organized and developed by two international societies. It is anticipated that this consensus will provide further guidance to urologists and may help to improve clinical outcomes for patients.
Keywords: Delphi Process; Expert Consensus; Retrograde Intrarenal Surgery